An Empirical Study into Identifying Project Complexity Management Strategies. (2016) - Kermanshachi, Sharareh; Dao, Bac; Shane, Jennifer; Anderson, Stuart
Abstract: Complexity is a term that is used throughout the construction industry. When complexity is poorly understood and managed, project failure become the norm. However, there are limited number of studies which investigated best practices which could overcome the undesired outcomes of complexity challenges. This research focused on identifying strategies to manage complexity in order to increase the likelihood of project success. Initially, this paper reviewed different project complexity definitions and suggested a single definition. Furthermore, the differences between complexity, uncertainty and risk were explained. Moreover, complexity management strategies were collected and enhanced. For this purpose, two rounds of qualitative Delphi method were applied to identify and improve complexity management best practices. In the first round, Subject Matter Experts were asked to individually provide top complexity management strategies. In the second round of this study, the twelve experts were participated in a complexity management workshop to advance the identified strategies.